Percutaneous cholecystoduodenal stent as a definite treatment for acute cholecystitis in elderly or comorbid patients: a bicentric retrospective study - Tae Yun Lee; Jong Woo Kim; Dong Jae Shim; Doyoung Kim; Young Chul Yoon; Edward Wolfgang Lee (Diagnostic and Interventional Radiology, 2023)

(untitled)
PURPOSETo investigate the safety and efficacy of percutaneous cholecystoduodenal stent (CDS) placement to prevent recurrence of acute cholecystitis in patients who were unfit for cholecystectomy.METHODSBetween April 2016 and January 2022, 46 patients [median age (range) = 81 (37–99) years; men = 15] with acute cholecystitis who were unfit for surgery underwent percutaneous cholecystostomy followed by a CDS placement in two institutions. Plastic stents of three different materials were used [polyethylene, polyurethane (PU), and polycarbonate (PCB)-based PU]. Clinical outcomes, including technical and clinical success rates and early (<30 days) and delayed adverse events, were retrospectively assessed by stent type.RESULTSCDS placement was technically successful in 39 patients. Clinical success, defined as cholecystostomy catheter removal, was achieved in 35 of 39 patients. Immediate complications, such as acute pancreatitis and peritonitis, occurred in two patients. Two patients experienced recurrent cholecystitis during a 113-day follow-up (range, 3–1,723). Three-stent groups had significantly different delayed complications on Fisher’s exact test (P = 0.021). The Bonferroni post-hoc analysis showed the PCB-PU group tended to have fewer complications than the PU group (P = 0.060).CONCLUSIONCDS placement is applicable in treating acute cholecystitis patients who were initially unfit for surgery, but further investigation is needed. Although it was not statistically significant, a PCB-PU stent can be suitable for this use because it tends to have fewer delayed complications and is equipped with a drawstring and side holes.